PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN PARTISIPASI BELAJAR SISWA KELAS RENDAH DI MI 03 WERU - Asfy Lailatul Hijjah (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to describe the implementation of the cooperative learning model as an effort to enhance learning participation among lower-grade students at MI 03 Weru. The research employed a descriptive qualitative approach with a sample of 20 second-grade students. Data were collected through classroom observations, interviews with the homeroom teacher, and documentation of learning activities. The findings indicate that the application of cooperative learning promotes increased student participation in verbal, social, motor, and emotional aspects. Students became more engaged in discussions, demonstrated improved teamwork, expressed their opinions more confidently, and showed greater enthusiasm during learning activities. These results reinforce that cooperative learning is highly relevant for lower-grade classrooms, as it optimizes learning interactions and enhances student activity. ABSTRAK Penelitian ini bertujuan mendeskripsikan penerapan model pembelajaran kooperatif sebagai upaya meningkatkan partisipasi belajar siswa kelas rendah di MI 03 Weru. Pendekatan penelitian menggunakan kualitatif deskriptif dengan subjek 20 siswa kelas II. Data diperoleh melalui observasi proses pembelajaran, wawancara dengan guru kelas, serta dokumentasi kegiatan belajar. Hasil penelitian menunjukkan bahwa penerapan pembelajaran kooperatif mendorong peningkatan partisipasi siswa dalam aspek verbal, sosial, motorik, dan emosional. Siswa lebih terlibat dalam diskusi, mampu bekerja sama dalam kelompok, berani menyampaikan pendapat, dan menunjukkan antusiasme dalam mengikuti kegiatan pembelajaran. Temuan ini memperkuat bahwa model pembelajaran kooperatif relevan diterapkan pada kelas rendah untuk mengoptimalkan interaksi belajar dan meningkatkan aktivitas siswa.